Effect of Al/Cu weight fraction on the mechanical and electrical properties of Al-Cu conductors for overhead transmission lines - Han, Deokhyun; Kim, Geon Hong; Kim, Jaesung; Ahn, Byungmin (Archives of Metallurgy and Materials, 2020)
In the past few years, overhead copper transmission lines have been replaced by lightweight aluminum transmission lines to minimize the cost and prevent the sagging of heavier copper transmission lines. High strength aluminum alloys are used as the core of the overhead transmission lines because of the low strength of the conductor line. However, alloying copper with aluminum causes a reduction in electrical conductivity due to the solid solution of each component. Therefore, in this study, the authors attempt to study the effect of various Al/Cu ratios (9:1, 7:3, 5:5) to obtain a high strength Al-Cu alloy without a significant loss in its conductivity through powder metallurgy. Low-temperature extrusion of Al/Cu powder was done at 350ºC to minimize the alloying reactions. The as-extruded microstructure was analyzed and various phases (Cu9Al4, CuAl2) were determined. The tensile strength and electrical conductivity of different mixing ratios of Al and Cu powders were studied. The results suggest that the tensile strength of samples is improved considerably while the conductivity falls slightly but lies within the limits of applications.
Keywords: Conductor lines; Electrical conductivity; High strength Al-Cu alloy; High strength aluminum alloys; Low temperature extrusion; Mechanical and electrical properties; Overhead transmission lines; Weight fractions; Aluminum; Extrusion; Intermetallic; Lightweight; Tensile; Transmission line